The neural crest transcription factor Brn3a is expressed in melanoma and required for cell cycle progression and survival. Issue 6 (13th May 2013) - Hohenauer, Tobias; Berking, Carola; Schmidt, Andreas; Haferkamp, Sebastian; Senft, Daniela; Kammerbauer, Claudia; Fraschka, Sabine; Graf, Saskia Anna; Irmler, Martin; Beckers, Johannes; Flaig, Michael; Aigner, Achim; et al.
Abstract Pigment cells and neuronal cells both are derived from the neural crest. Here, we describe the Pit‐Oct‐Unc (POU) domain transcription factor Brn3a, normally involved in neuronal development, to be frequently expressed in melanoma, but not in melanocytes and nevi. RNAi‐mediated silencing of Brn3a strongly reduced the viability of melanoma cell lines and decreased tumour growth in vivo. In melanoma cell lines, inhibition of Brn3a caused DNA double‐strand breaks as evidenced by Mre11/Rad50‐containing nuclear foci. Activated DNA damage signalling caused stabilization of the tumour suppressor p53, which resulted in cell cycle arrest and apoptosis. When Brn3a was ectopically expressed in primary melanocytes and fibroblasts, anchorage‐independent growth was increased. In tumourigenic melanocytes and fibroblasts, Brn3a accelerated tumour growth in vivo. Furthermore, Brn3a cooperated with proliferation pathways such as oncogenic BRAF, by reducing oncogene‐induced senescence in non‐malignant melanocytes. Together, these results identify Brn3a as a new factor in melanoma that is essential for melanoma cell survival and that promotes melanocytic transformation and tumourigenesis.